The Effect of Demographic Dividend, HDI, and Population Growth on Economic Growth in East Java - Hidayat, Saiful; Prabowo, Prayudi (Jurnal Ekonomika : INDEPENDEN, 2024)
The objective of this research is to assess the impact of independent variables, specifically demographic dividend utilizing dependency ratio data, the Human Development Index (HDI), and population growth, on the economic growth of districts and cities in East Java from 2010 to 2020. The research employed a quantitative methodology, utilizing secondary data sourced from the official website of BPS East Java Province.. The data analysis method uses panel data linear regression. The result shows that the demographic dividend variable, which uses data on dependency ratio, Human Development Index (HDI), and population grwoth, partially has a negaive and significant influence on district/city economic growth in East Java. Then all independent variables have a simultaneous influence on district/ city economic growth in East Java.